Effects of isoproterenol on regional myocardial function, electrogram, and blood flow in conscious dogs with myocardial ischemia. - Vatner, S F (1976)
The effects of coronary occlusion and of subsequent isoproterenol infusion were examined in conscious dogs. Left ventricular (LV) function was assessed by measurements of LV diameter, pressure, velocity and dP/dt/P, and regional myocardial function was assessed by measurements of segment length (SL) and velocity of SL shortening in normal, border, and ischemic zones. Regional myocardial function was measured from the same sites, along with intramyocardial electrograms and regional myocardial blood flow as determined by radioactive microspheres. Coronary occlusion resulted in graded loss of function from the normal to severely ischemic zones with graded flow reductions and graded increases in ST segment elevation. Isoproterenol improved overall LV function, and function in the normal zone. Isoproterenol also improved function in 19 of 21 border-zone segments and in all moderately ischemic segments, while elevating further the ST segments. These changes were accompanied by increases in myocardial blood flow. In contrast, in severely ischemic segments, isoproterenol resulted in a deterioration of function, in that paradoxical motion occurred in segments previously akinetic during systole, while paradoxical motion was intensified in those segments in which it was already present. These changes were accompanied by further ST segment elevation but not by concurrent increases in blood flow. In addition, in 2 of 21 border zone segments, myocardial blood flow fell and these segments responded to isoproterenol with complete loss of function; paradoxical motion developed. Thus, in the conscious dog, a strong inotropic agent can improve function, even in the ischemic myocardium, as long as the required additional blood flow can be provided wither through primary or collateral channels.